Optimizing Educational Facilities and Infrastructure Management: Operational Standards with Ergonomic Principles - Rondo, Muhammad Raihan; Muhammad, Mutsanna Bin (Proceeding International Conference on Religion, Science and Education, 2025)
Research on ergonomics in educational facilities and infrastructure is still very limited. It is important to conduct research related to ergonomics in education to produce optimal management of facilities and infrastructure. Optimizing the management of facilities and infrastructure will have a good effect on educational institutions. This study aims to analyze the application of ergonomic principles in operational standards in the management of educational facilities and infrastructure. The background of this study is based on the increasing attention to the health and comfort of users in the educational environment, which affects the effectiveness of learning. The method used in this study is literature analysis from various sources, including journal articles, books and research reports related to ergonomics and educational infrastructure. The results show that the application of ergonomic principles can improve students’ physical comfort, reduce the risk of injury, and support a more productive learning atmosphere. This is because ergonomic principles always prioritize linkages and connections between facilities and infrastructure and operational standards. The conclusion of this study emphasizes the importance of integrating ergonomic principles in the design and management of educational facilities and infrastructure to achieve optimal educational outcomes.